Unraveling NK cell heterogeneity through single-cell sequencing: insights from physiological and tumor contexts for clinical applications - Shen, Mingxin; Liu, Yutong; Shao, Liang; Qu, Meng; Song, Shixin; Sun, Wei; Zhang, Hao (Frontiers in Immunology, 2025)
Natural killer cells (NK cells) are important immune cells within the tumor microenvironment (TME) and are considered the first line of defense in tumor immunity. Although many studies have focused on the role of NK cells in tumor therapy, the heterogeneity of NK cells complicates the investigation of the complex mechanisms within the tumor microenvironment. Single-cell sequencing technology, with its high-resolution capability, reveals the gene expression profiles of individual NK cells, highlighting their heterogeneity and providing more accurate information for NK cell therapy. This article begins by addressing the mechanisms underlying the formation of NK cell heterogeneity, emphasizing the significance of differentiation, development, and tissue residency in establishing this heterogeneity. It also summarizes the advances in the study of NK cell heterogeneity under physiological conditions and in tumor environments using single-cell sequencing technology. Finally, it analyzes the dynamic changes of NK cells within the tumor microenvironment under various therapeutic approaches to explore drug effects and resistance mechanisms, as well as to optimize therapeutic options. Investigating the mechanisms of tumor progression and drug intervention at the single-cell level will provide new perspectives for personalized treatment strategies centered around NK cells.